CONSUMERS' VISUAL ATTRACTIVENESS TO DMS IN TRAVEL ADVERTISEMENTS: AN EYETRACKING TEST: Received: 6th January 2025, Revised: 14th February 2025, 26th February 2025, Accepted: 2nd April 2025, Date of Publication: 15th July 2025 - Lin, Yi-Shan, (PUPIL: International Journal of Teaching, Education and Learning, 2025)
In recent years, with the booming development of sightseeing tourism, the dissemination of tourism information has become more rapid and extensive, and tourism advertising DM has become one of the important marketing tools to attract customers. Different designs of travel advertisement DMs will have an impact on consumers' purchase intention. In this study, we used eye-tracking tests to investigate the visual attractiveness of DM travel advertisements and to analyze the eye-movement responses of secondary school teachers when they viewed such advertisements. The content of the advertisements consisted of four main elements, namely, the main headline of the tour, the promotional image, the price and the brand name of the tour company. 53 secondary school teachers were invited to participate in the eye-tracking test. The results of the study showed that teachers' eye-movement responses and visual attractiveness were mainly influenced by the main headline of the travel advertisement and the promotional image, whereas branding and price had less influence. Therefore, the design of the main headline and images in travel advertisements plays a key role in attracting consumers' attention and influencing their decision-making time.